IMPLEMENTASI PKWT DAN PKWTT DALAM PRAKTIK KETENAGAKERJAAN SERTA DAMPAKNYA TERHADAP KEPASTIAN HUKUM - Tanjung Pamungkas (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Fixed-Term Employment Agreement (PKWT) and Indefinite-Term Employment Agreement (PKWTT) are two forms of employment agreements regulated within the labor system in Indonesia as the basis for establishing working relationships between workers and employers. PKWT is used for temporary or time-limited work, while PKWTT is intended for permanent and ongoing work. This research aims to analyze the implementation of PKWT and PKWTT in labor practices and their impact on legal certainty for the parties involved. The method used is a normative juridical approach by examining the applicable laws and regulations as well as literature related to employment. The discussion results show that PKWT provides flexibility for employers in managing the workforce, but in practice, it often creates uncertainty for workers, especially when there are deviations from the applicable legal provisions. Meanwhile, PKWTT provides stronger certainty for workers in terms of the continuity of the employment relationship and legal protection, although on the other hand, it imposes greater obligations on employers. The implementation of these two types of employment agreements is greatly influenced by the level of compliance with regulations, the effectiveness of supervision, and the parties' understanding of the applicable legal provisions.